Fundamentals of Modern Unsteady Aerodynamics - Gülçat, Ülgen; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
In this book, the author introduces the concept of unsteady aerodynamics and its underlying principles. He provides the readers with a comprehensive review of the fundamental physics of free and forced unsteadiness, the terminology and basic equations of aerodynamics ranging from incompressible flow to hypersonics. The book also covers modern topics related to the developments made in recent years, especially in relation to wing flapping for propulsion. The book is written for graduate and senior year undergraduate students in aerodynamics and also serves as a reference for experienced researchers. Each chapter includes ample examples, questions, problems and relevant references.   The treatment of these modern topics has been completely revised end expanded for the new edition. It now includes new numerical examples, a section on the ground effect, and state-space representation.
Introduction -- Fundamental Equations -- Incompressible Flow About an Airfoil -- Incompressible Flow About Thin Wings -- Subsonic and Supersonic Flows -- Transonic flow -- Hypersonic Flow -- Modern Subjects -- Aerodynamics: The Outlook for the Future.
Keywords: Aerospace engineering; Astronautics; Physics; Fluid mechanics; Aerospace Technology and Astronautics; Classical and Continuum Physics; Engineering Fluid Dynamics